Valve Surgery at the Turn of the Millennium - Peels, C. H.; Baur, L. H. B. (Developments in Cardiovascular Medicine, 2004)
Valve Surgery at the Turn of the Millennium covers valvular heart disease in the aortic and mitral valves in the adult patient. Special attention is given to the important issue of optimal timing, the role of echocardiography in the peri-operative period and assessment of adequate prosthetic valve function and dysfunction. New developments in valvular surgery are discussed and the surgical view on choice of valve replacement devices and of the approach of endocarditis is reviewed.